Physical, Chemical and Organoleptic Characteristics of Lactose-Free Milk-Based Ice Cream - Arifin, Muhamad; Detiara, Azzahra; Arief, Irma Isnafia; Soenarno, Moch. Sriduresta; Fajr, Aulia Irhamni; Wulandari, Zakiah; Suryati, Tuti; Apriantini, Astari; ., Salundik; Murtini, Devi; Budiman, Cahyo; Taufik, Epi (Unpad Press, 2025)
Lactose-intolerant individuals avoid consuming milk and dairy products, which may lead to deficiencies in essential nutrients naturally present in milk. Lactose-free milk, characterized by its higher sweetness compared to full-cream milk, serves as an ideal base for ice cream—a widely consumed product valued for its sweetness and unique texture. This study aims to analyze the physical, chemical and organoleptic characteristics of lactose-free ice cream. Lactose-free milk was produced using 0.2% lactase enzyme. The evaluated parameters included viscosity, overrun, melting time, pH, sweetness level, total caloric content, lactose content, and organoleptic properties. Data were analyzed using a t-test by comparing ice cream made with whole milk and lactose-free milk. The results indicated that lactose-free ice cream exhibited a significantly higher overrun (p < 0.05), a sweeter taste, and lower total caloric content. However, it had a shorter melting time. No significant differences (p > 0.05) were observed in viscosity, pH, or organoleptic properties. These findings suggest that lactose-free ice cream demonstrates a comparable level of consumer acceptance to whole milk-based ice cream. Keywords: ice cream, lactase, lactose free milk, lactose intolerant, whole milk